Risk Assessment of Heavy Metal Exposure from Sinanodonta woodiana in Krueng Meureubo River, West Aceh - Qoriansas, Nanda; Sahwadi, Ira; Rahmayati, Riski; Andriani, Rizki (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2026)
The increasing intensity of industrial activities in the coastal area of West Aceh has the potential to contaminate aquatic environments with heavy metals such as chromium (Cr), lead (Pb), and mercury (Hg), which can accumulate in aquatic biota and pose health risks to humans. This study aimed to analyze the concentration of heavy metals in Sinanodonta woodiana, assess community exposure levels based on consumption patterns, and estimate non-carcinogenic health risks using the Environmental Health Risk Assessment (EHRA) approach. The study was conducted at four sampling sites along the Krueng Meureubo River and involved 141 respondents. Heavy metal concentrations were analyzed using Atomic Absorption Spectrophotometry, while health risks were assessed based on daily intake and Hazard Quotient (HQ) values. The results indicated that Pb (2.36–5.65 mg/kg) and Hg (1.10–53.27 mg/kg) concentrations in mussel tissue exceeded national food safety limits, whereas Cr concentrations (<0.0001 mg/kg) remained within acceptable levels. Risk characterization showed that 71.7% of respondents had HQ values greater than 1 for Pb and Hg, indicating potential non-carcinogenic health risks associated with regular mussel consumption. In contrast, Cr exposure did not present a significant health risk. These findings highlight that the consumption of freshwater mussels from the Krueng Meureubo River may pose health risks to coastal communities, underscoring the need for continuous monitoring of water quality and aquatic food safety to prevent long-term adverse health effects.